Optimizing Cognitive Support & Standardization: Digital Transformation of Production Instruction Systems in Manufacturing - An evaluation of current system and possible digitalization solutions - Bergström Ohlsson, Amanda; Holmgren Faghihi, Linda (My University, 2025)
In the face of increasing production complexity and higher quality demands in the manufacturing industry, effective cognitive support for operators has become crucial. This thesis investigates the current state of production instruction systems at Scania’s transmission factory and explores opportunities for digital transformation to enhance efficiency, standardization, and user experience. The existing production instruction system at Scania CV AB, based on printed documents generated through the ArtHur software, presents significant challenges in terms of usability, cognitive load, and standardization across departments. Through a combination of a system atic literature review, qualitative methods, including interviews, Gemba walks, and workshops, and a benchmarking study with peer companies, key shortcomings and improvement areas were identified. A requirement specification was developed to guide the design of two conceptual solutions: one for immediate implementation based on improved standards, and one representing a state-of-the-art digital sys tem. A pilot project was conducted to evaluate both concepts in a real production setting. Results demonstrate the potential of intuitive digital interfaces to reduce operator cognitive load, improve instruction accessibility, and support standardized procedures. The findings offer actionable recommendations for implementing more effective, user-centered instruction systems in machining environments.
Keywords: cognitive support; work instructions; digital transformation; machining; standardization; Industry 4.0; user interface; production engineering